Analisis Kuat Arus dan Wire Speed Pada Permesinan Wire Cut EMS 45 Terhadap Kekasaran Permukaan Roda Gigi Lurus - Muas M; Rusdi Nur; Usman Usman; Firman Arif (Jurnal Teknik Mesin Sinergi, 2020)
Wire cut is a high-tech machining process and can be used to make high-precision products. This study aims to analyze the results of the workpiece surface and study the effect of current strength and wire speed on wire cut machining of EMS 45 on the surface roughness of straight gears. The results analyzed were the surface roughness values obtained by testing the surface roughness. The variations in the current used were 3 amperes, 5 amperes, and 7 amperes, while the wire speed used was 8 mm / min, 10 mm / min, and 12 mm / min. In the wire cut machining process, brass cutting materials are used with a wire diameter of 0.25 mm. The results showed that the greater the current and wire speed used, the lower the surface roughness value, conversely the smaller the current and the wire speed used, the higher the surface roughness value. The results of data analysis using the ANOVA analysis method, correlation, and regression get the optimal conditions for obtaining low surface roughness values and fast cutting time, namely at a current of 7 amperes with a wire speed of 10 mm/min.